Leaves and barks of Albizia shade trees in tea plantation shows both insect attractant and pesticidal properties: a GC-MS based investigation (Asian Journal of Agriculture, 2021)
Abstract. Ghosh A, Majumder S, Saha S, Chakraborty S, Bhattacharya M. 2021. Leaves and bark of Albizia shade trees in tea plantation show both insect attractant and pesticidal properties: a GC-MS based investigation. Asian J Agric 5: 84-89. Tea is the major plantation crop of sub-Himalayan region. The bushes are grown under a partial canopy cover of leguminous plants to protect them from scorching sun rays. The shade plants are primarily beneficial but attract several pests. Metabolites present in four Albizia trees were detected by GC-MS, and insect attracting and/or repelling phytochemicals were pointed out. A total of thirty-two compounds exhibiting semiochemical properties were detected. 15.84%, 2.52%, 2.61% of semiochemicals are exclusively present in leaves of Albizia odoratissima, Albizia chinensis, and Albizia procera. While in bark 10.73% and 13.35% semiochemicals were exclusively present in Albizia odoratissima and Albizia lebbeck. A total of nine semiochemicals are exclusively present in AO, out of which seven semiochemicals viz., caryophyllene, epoxide; longiborneol; longifolene; methyl linolenate; methyl linoleate; methyl cis-jasmonate; tonalid are present in leaf and five semiochemicals viz. longiborneol; methyl cis-jasmonate; camphor; isopropyl myristate; tonalid are present in bark. A total of five semiochemicals viz. alpha-santalol; bisabolol oxide A; gamma-Sitosterol; glycidyl oleate (as oleic acid); oleoyl chloride (as oleic acid) are found exclusively in the bark of Albizia lebbeck.  There were only three semiochemicals that were exclusively found in the leaf of AC, these were 2-decen-1-ol; cyclohexanol, 5-methyl-2-(1-methyl ethyl); acetophenone.  In the leaf of AP, a total of five semiochemicals were found to be exclusive, these being dehydro-beta-ionone; oleamide; beta-amyrin; isopropyl linoleate; stigmasterol. GC-MS analysis explored metabolites from shade trees like caryophyllene, epoxide; beta-amyrin; 1, 8-cineol etc. which serve as both attractant and pesticidal components while compounds like longiborneol; longifolene; linalyl acetate, etc. are exclusively pest attractants and compounds like isopropyl myristate are exclusive pest repellants. This cumulative property of shade trees can be utilized to trap insect pests and destroy them with pesticidal activity. Isolation of these metabolites from shade trees, and their utilization as semiochemical/pheromone trap and green pesticides, will control pests by eco-friendly measures along with reducing the production cost.